Kondisi Optimum untuk Produksi Kitinase dari Streptomyces Rkt5 dan Karakterisasi pH dan Suhu Enzim - Yurnaliza, Yurnaliza; Margino, Sebastian; Sembiring, Langkah (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Chitinase is chitin degrading enzyme which is produced by Streptomyces Rkt 5 is isolated microorganism from peanut rhizosfer. This enzyme and its microorganism can be used in many agricultural, medicine and industrial purposes. The aim of the research was to find out the optimum condition for production of chitinase and to characterize of pH and temperature to chitinase activity. Optimalizing production the research had 4 treatments. The optimum conditions were achieved at mineral liquid medium containing with chitin 0,2% (w/v) as inducer, 10% (v/v) inoculum, pH 7 and 48 hours incubation. The crude enzyme was partially purified by salting out with 70% ammonium sulfate resulted in 3.31 time more purity enzyme than the crude one. This enzyme had maximum activity at 50oC and pH 5.5.